The Effect of Oil Thickness in the Cylindrical Settling Tank on the Moisture and Impurities of Crude Palm Oil (CPO) - St. Nugroho Kristono; Istianto Budhi Rahardja; Ali Darmawan (Journal of Applied Sciences and Advanced Technology, 2020)
Cylindrical Settling Tank (CST) is a unit of clarification station that functions as a process of placing and extracting / extracting palm oil using the under flow and upper flow processes of palm oil. A clarification station is a station in a palm oil mill which functions to separate oil, water, sludge and other objects involved in the refining process of palm oil. This process aims to obtain clean palm oil and avoid dirt and water levels during the extraction process. The higher / thicker the oil layer is taken, it will affect the quality of the palm oil obtained, so it is carried out by taking palm oil slowly (laminar flow). Taking the height / thickness of palm oil is carried out on a skimmer unit that can rise and fall from the surface of the palm oil using a screw system. The results of taking the height / height of palm oil from the level of 20 cm, 30 cm, and 40 cm with the average yield of water content and CST feed impurities are 29.125% and 38.931%, the average output of the Skimmer for moisture and moisture content. the impurities are 1.039% and 0.089%. The mean wet oil tank output was 0.956% and 0.037%, and the mean moisture content and dirt content of the vaccum drier were 0.196% and 0.021%.